Students’ Perceptions of the Educational Environment in Relation to Nationalism Values at Pamulang University - Putri, Fuzy Helminia (Universitas Pamulang, 2026)
This study on Students’ Perceptions of the Educational Environment in Relation to Nationalism Values was motivated by the need to explore how Pamulang University students understand and internalize nationalism values within their academic and social lives. The research employed a qualitative approach using phenomenological methods. Data were collected through in-depth interviews, observation, and documentation. Informants consisted of students, lecturers, and the head of the study program. The findings indicate that students’ perceptions encompass cognitive, affective, and conative dimensions. The internalization of nationalism values occurs through academic pathways such as lectures and coursework and socio-practical pathways including student organizations, cultural activities, and community service. Supporting factors include lecturer involvement, relevant course material, and active student participation, while inhibiting factors include overly theoretical teaching methods, limited creative platforms for cultural expression, and the influence of foreign popular culture. In conclusion, Pamulang University students demonstrate diverse understandings of nationalism, reflected across cognitive, affective, and conative dimensions. The internalization process occurs through a combination of institutional-academic channels and socio-practical experiences, highlighting the strategic role of the university’s educational environment in shaping students’ perceptions of nationalism values.